Thunder rolling down the mountain : the story of Chief Joseph and the Nez Perce - Biskup, Agnieszka (Graphic library. American graphic., 2011)
In graphic novel format, explores the battles and hardships faced by Chief Joseph and the Nez Perce when they were forced to leave their homelands.